Academic Application Design WEB-based on junior high schools - Baenil Huda; Fitri Nurapriani; Helga Amanda (Buana Information Technology and Computer Sciences (BIT and CS), 2020)
Current advances in information technology have provided great benefits in the world of education, making web-based academic applications is a major use of information technology. Information technology enables academic data to be processed and, making the required presentation of academic information be got, and. This research uses technological trends in managing academic administration so that conventional bookkeeping in junior high schools is overcome by computer systems. The method in developing the system uses a waterfall with WEB-based device implementation. The application of this new system can improve the knowledge and skills of employees, teachers, and principals in web-based academic applications.